2016
DOI: 10.1021/acs.jpcc.5b10240
|View full text |Cite
|
Sign up to set email alerts
|

Ladder-Type Silsesquioxane Copolymer Gate Dielectrics for High-Performance Organic Transistors and Inverters

Abstract: A ladder-type poly­(phenyl-co-methacryl silsesquioxane) (PPMSQ) copolymer was developed for use as a gate dielectric in high-performance organic field-effect transistors (OFETs). The ladder-type PPMSQ copolymer was synthesized via the hydrolysis of two types of monomers, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane, followed by a condensation polymerization. The phenyl groups in one monomer were introduced to enhance the structural ordering of the overlying organic semiconductors, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Finally, it has to be pointed out that contact angle measurements confirm that particle-loaded coatings can still be considered smooth, from a wetting perspective, since neither a Wenzel state (i.e., significant increase in contact angle hysteresis) nor a Cassie-Baxter state (i.e., superhydrophobic wetting state) are observed. This result is not unexpected, since silsesquioxane-based polymer nanocomposites display smooth surfaces in general [71,72].…”
Section: Samplementioning
confidence: 57%
“…Finally, it has to be pointed out that contact angle measurements confirm that particle-loaded coatings can still be considered smooth, from a wetting perspective, since neither a Wenzel state (i.e., significant increase in contact angle hysteresis) nor a Cassie-Baxter state (i.e., superhydrophobic wetting state) are observed. This result is not unexpected, since silsesquioxane-based polymer nanocomposites display smooth surfaces in general [71,72].…”
Section: Samplementioning
confidence: 57%
“…The reported dielectric films formed at a curing temperature of 200 • C exhibited a leakage current density as low as 6 × 10 −9 A·cm −2 at 1 MV·cm −1 [45]. Similarly, Kim et al reported dielectric materials based on a silsesquioxane derivative containing cage-structured epoxy groups, and the resulting films showed a leakage current density of ≈10 −8 A·cm −2 at 1 MV·cm −1 [46].…”
Section: Introductionmentioning
confidence: 83%
“…To this end, many studies on the development and application of new dielectric materials with low leakage current, high dielectric constant, and facile process have been reported [39][40][41][42][43][44][45][46][47][48]. Among them, organic-inorganic hybrid dielectrics might synergistically combine the advantages of both materials, i.e., the excellent mechanical and electrical properties of inorganics and the flexibility and large area solution processibility of organics [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have fabricated the SiO 2 layer by conversion of spin-on-glass (SOG) materials such as perhydropolysilazane (PHPS), silsesquioxane, tetraethyl orthosilicate, and tetramethyl orthosilicate. [20][21][22][23][24] Because of the low cost, simplicity, and excellent substrate adaptability of this approach, this process can replace the conventional vapor deposition process. PHPS, used in this study, is one of the most widely used SOG materials because of its low carbon contamination and ability to form dense lms.…”
Section: Introductionmentioning
confidence: 99%